Effectiveness of Islamic-spiritual Skills Training on Spiritual Vitality and Emotional Adjustment in Mothers. - Shahzehpour, Abdoulghader; Nakhaei, Somayeh; Etemadinia, Samira; Haghighat, Amir Golbandi (Health, Spirituality & Medical Ethics Journal, 2026)
Background and Objectives: Mothers of children with learning disabilities (LD) are at risk of mental exhaustion, decreased spiritual vitality, and decreased emotional adjustment due to continuous training, educational, and psychological challenges. The present study aimed to investigate the effectiveness of Islamic-spiritual skills training on the spiritual vitality and emotional adjustment of mothers of children with LD. Methods: The present study employed a quasi-experimental study with a pretest-posttest design with a control group. A sample of 50 mothers of children with LD from the cities of Zabol and Zahedan in 2024 was selected using purposive sampling and randomly assigned to two experimental and control groups (25 people each). The experimental group received 12 90-minute sessions of Islamic-spiritual skills training based on the revised Galanter & Siegel protocol, while the control group received no intervention. The data collection tools included the standard questionnaires of spiritual vitality by Chirian and Afrooz and emotional adjustment by Farahbakhsh. The data were analyzed using the multivariate analysis of covariance (MANCOVA) test in SPSS software, version 26. Results: The research findings showed that training in Islamic spiritual skills had a significant effect on increasing spiritual vitality (F=117.35) and improving emotional adjustment (F=98.45) of mothers in the experimental group compared to the control group (P<0.05). These results indicated the effectiveness of the Islamic spiritual package in improving the psychological components of mothers. Conclusion: The findings of this study indicate that training in Islamic spiritual skills can be used as an effective, indigenous, and cultural intervention in promoting the mental health of mothers of children with LD.